Hubungan Status Gizi dan Aktivitas Fisik Dengan Keteraturan Siklus Menstruasi Pada Remaja Putri di SMAN Colomadu Desa Baturan - Putri, Annisa Mulyarani; Sarbini, Dwi (LPPM Institut Pendidikan Nusantara Global, 2025)
Puberty in adolescent girls is typically marked by the onset of menstruation, with the menstrual cycle defined as the interval from the first day of one period to the first day of the next. For some adolescents, this cycle may be irregular. Factors suspected to influence cycle regularity include nutritional status, physical activity, stress levels, and age at menarche. In response to this issue, a study was conducted to evaluate whether there is a relationship between nutritional status and physical activity with menstrual cycle regularity in adolescent girls. This study employed a quantitative approach using a correlational method and a cross-sectional research design. The sample consisted of 57 tenth-grade students from SMAN Colomadu selected randomly. Data analysis revealed no significant relationship between nutritional status and menstrual cycle regularity, with a p-value of 0.233. Similarly, physical activity did not show a meaningful association with cycle regularity, indicated by a p-value of 0.055. Based on these findings, it can be concluded that among tenth-grade students at SMAN Colomadu, nutritional status and physical activity do not have a significant impact on menstrual cycle regularity.